2006
DOI: 10.1021/jp064384c
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic and Electronic Structure of Semimetallic Sb and Semiconducting AlSb Fabricated by Nanoscale Electrodeposition:  An in Situ Scanning Probe Investigation

Abstract: The nanoscale electrocrystallization of pure Sb and the compound semiconductor AlSb on Au(111) has been studied by in situ scanning probe techniques (STM and STS) employing an ionic liquid electrolyte, {AlCl3-[C4mim]+Cl-} (1:1) containing SbCl3. The characteristic changes of the electronic structures with varying potentials have been probed for the first time by normalized differential conductance spectra, (dI/dU)/(I/U). In the underpotential deposition range of Sb the formation of two layers is observed. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 25 publications
5
18
0
Order By: Relevance
“…[32,113] The systems include elemental semiconductors of Ge [115][116][117][118][119] and Si [120] and composite semiconductors of Si x Ge 1Àx , [121] ZnTe, [122] CdTe, [123] , InSb, [124] AlSb, [125,126] and ZnSb. [127] More recently, efforts have been devoted to the preparation of functionalized and nanostructured semiconductors, [128][129][130][131] including nanowires of Ge [128] , Si, [128] and Si x Ge 1Àx [130] as well as three-dimensional ordered macroporous Ge.…”
Section: Initial Stage Of Metal Electrodepositionmentioning
confidence: 99%
See 2 more Smart Citations
“…[32,113] The systems include elemental semiconductors of Ge [115][116][117][118][119] and Si [120] and composite semiconductors of Si x Ge 1Àx , [121] ZnTe, [122] CdTe, [123] , InSb, [124] AlSb, [125,126] and ZnSb. [127] More recently, efforts have been devoted to the preparation of functionalized and nanostructured semiconductors, [128][129][130][131] including nanowires of Ge [128] , Si, [128] and Si x Ge 1Àx [130] as well as three-dimensional ordered macroporous Ge.…”
Section: Initial Stage Of Metal Electrodepositionmentioning
confidence: 99%
“…Systematic in situ STM investigations of the UPD of these two systems have been carried out on Au singlecrystalline electrodes, which demonstrate a significant "solvent effect" from ionic liquids. [22,67,69,125,126,151,152] The results from the authors' group in [BMI] [BF 4 ] [22,67,69,153] are highlighted as follows.…”
Section: Semimetal Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrodeposition of AlSb in ionic liquids was investigated by several groups. It was reported that AlSb can be electrodeposited on Au (111) [34,35]. In situ probe techniques were used to study the electrodeposition of the semiconductor.…”
Section: Alsbmentioning
confidence: 99%
“…One of them is AlSb, which has wide variety applications e photovoltaic cells, pen junction diodes, and anodes for Li-ion batteries [1]. It is zinc-blende structure with a lattice constant of 0.6126 nm [2,3], and high melting point (1058 C) [4]. It shows sharp-line donor-acceptor pair spectrum, caused by electron-hole transition process [2].…”
Section: Introductionmentioning
confidence: 99%